2011
DOI: 10.2217/fca.11.43
|View full text |Cite
|
Sign up to set email alerts
|

Is γ-glutamyl Transferase Activity a Potential Marker of Left Ventricular Function During Early Postmyocardial Infarction period?

Abstract: GGT is associated with oxidative/inflammatory markers and LV diastolic diameter suggesting its potential role in predicting LV dilatation and dysfunction during the early postmyocardial infarction period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…We observed higher serum GGT levels associated with mortality in men and women in correlation with other studies (33)(34)(35)(36). In the subgroup analysis of survivors or non-survivors, we did not observe a relationship with a history of DM, HT, or coronary heart disease.…”
Section: Discussionsupporting
confidence: 88%
“…We observed higher serum GGT levels associated with mortality in men and women in correlation with other studies (33)(34)(35)(36). In the subgroup analysis of survivors or non-survivors, we did not observe a relationship with a history of DM, HT, or coronary heart disease.…”
Section: Discussionsupporting
confidence: 88%
“…This finding triggered the studies focusing on the usefulness of GGT as a predictor of cardiovascular diseases. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] For the time being, this laboratory test has been searched by many groups regarding its suitability as a significant predictor for cardiometabolic diseases. Serum GGT was found to be a risk factor for cardiovascular mortality by the Vorarlberg Health Monitoring and Promotion Program Study Group.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Recent studies have reported that serum GGT, which is an inexpensive and easily accessible laboratory test, is a predictor for incident cardiovascular diseases, and is associated with prognosis in cardiopulmonary disorders such as coronary artery disease, acute myocardial infarction, HF, and acute pulmonary embolism. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] However, the prognostic significance of GGT in patients presenting with acute coronary syndrome (ACS) with left ventricular systolic dysfunction (LVSD) has not been searched yet. We hypothesized that increased admission serum GGT activity may be associated with future acute HF in ACS patients with LVSD.…”
mentioning
confidence: 99%
“…One prior study reported that serum GGT predicted LV dilation and dysfunction in 40 patients with acute myocardial infarction. 17 To the best of our knowledge, our study is the first to demonstrate an association between serum GGT levels and the prevalence of LV diastolic dysfunction and LVH in a large cohort of adults without prior evidence of heart disease.…”
Section: Study Limitationsmentioning
confidence: 58%
“…Only one study found that serum GGT predicted LV dilation and dysfunction in 40 patients with acute myocardial infarction. 17 To date, the relationship between serum GGT levels and LV function has not been studied using large cohorts of healthy adults.…”
mentioning
confidence: 99%